2020
DOI: 10.48550/arxiv.2009.05654
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Reinforcement Learning for Optimal Primary Frequency Control: A Lyapunov Approach

Abstract: The increase in penetration of inverter-based resources provide us with more flexibility in frequency regulation of power systems in addition to conventional linear droop controllers. Because of the fast power electronic interfaces, inverterbased resources can be used to realize complex control functions and potentially offer large gains in performance compared to linear controllers. Reinforcement learning has emerged as popular method to find these nonlinear controllers by parameterizing them as neural networ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 18 publications
1
18
0
Order By: Relevance
“…However, their approach only applies to the frequency control application, while our method works for voltage control which requires a different Lyapunov function design. Interestingly, both our work and prior work [37] arrive at a similar stability condition, that is strict policy monotonicity guarantees system stability.…”
Section: Introductionmentioning
confidence: 69%
See 2 more Smart Citations
“…However, their approach only applies to the frequency control application, while our method works for voltage control which requires a different Lyapunov function design. Interestingly, both our work and prior work [37] arrive at a similar stability condition, that is strict policy monotonicity guarantees system stability.…”
Section: Introductionmentioning
confidence: 69%
“…There are different approaches for monotone neural network architecture design in literature [37], [41], [42]. In this paper we follow the monotonic neural network design in [37, Lemma 3], which used a single hidden layer neural network with d hidden units and ReLU activation.…”
Section: B Algorithm Designmentioning
confidence: 99%
See 1 more Smart Citation
“…To this end, we formulate the controller with a stacked-ReLU structure shown in Fig. 3, which is developed in [27]. This design is a piecewise linear function where the slope of each piece is equal to the summation of weights in activated neurons.…”
Section: Design Of Stabilizing Neural Network Controllersmentioning
confidence: 99%
“…In addition, compared to rule-based algorithms, RL methods can learn directly from experiences without constructing an expert dataset [2], [10]. Learning-based control paradigms have been proposed for a variety of operation tasks in power grids, including control of voltage and frequency [11]- [14], capacity scheduling of PV and energy storage [15], topology control [1] and many more. A more detailed review of RL for power system operation can be found in [10].…”
Section: A Related Workmentioning
confidence: 99%